Pengaruh Gaya Kepemimpinan Situasional Dan Motivasi Kerja Terhadap Komitmen Dan Prestasi Kerja Karyawan Rumah Sakit Anak Dan Bersalin Muhammadiyah Tuban - Budi Widianto, Agung (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2013)
Hospitals as one form of business services for the community-oriented services in the field of health care is not much different form other endeavors. Understanding of the hospital is an institution of health care professionals whose services are provided by doctors, nurses and other health experts. Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban located at Jalan Diponegoro No. 1 Tuban with type "C". This study aims to prove and analyze the theory of situational leadership styles and motivation as applied to Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban does have a significant relationship with commitment and job performance of employees Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban. The population of this study are employees of Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban. Sampling was conducted with a total sampling / census of the employees Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban, as many as 120 people and responded to as many as 114 pieces or 95% of the total workforce Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban. Data collected through questionnaires and then processed using the Stuctural Equation Modelling operated through the program insisted AMOS 16.0.Finally, this study provides recommendations to Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban evaluation materials and standards to regulate or manage the hospital employee with either through the application of situational leadership style, and compliance with the appropriate motivation. As well as for academics in order to make the study materials that will enrich the science, particularly related to the situational leadership style, work motivation, employee commitment, and job performance of employees.Â Keywords : Situational Leadership , Work Motivation , Commitment to Work, Performance Work